2012
DOI: 10.1016/j.ajhg.2012.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Cantú Syndrome Is Caused by Mutations in ABCC9

Abstract: Cantú syndrome is a rare disorder characterized by congenital hypertrichosis, neonatal macrosomia, a distinct osteochondrodysplasia, and cardiomegaly. Using an exome-sequencing approach applied to one proband-parent trio and three unrelated single cases, we identified heterozygous mutations in ABCC9 in all probands. With the inclusion of the remaining cohort of ten individuals with Cantú syndrome, a total of eleven mutations in ABCC9 were found. The de novo occurrence in all six simplex cases in our cohort sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
121
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(131 citation statements)
references
References 33 publications
4
121
1
5
Order By: Relevance
“…POEMS syndrome ( polyneuropathy, organomegaly, endocrinopathy, M-protein, and skin changes) is a multisystem disorder associated with plasma cell dyscrasia, and patients with POEMS syndrome show up-regulated serum levels of angiogenetic factors including VEGF (vascular endothelial growth factor) and HGF (hepatocyte growth factor) (Yamada et al 2013). Cantu syndrome, characterized by hypertrichosis, macrosomia, osteochondrodysplasia, and cardiomegaly, is reported to be caused by mutations in ABCC9 (ATP-binding cassette, subfamily C, member 9) (van Bon et al 2012). McCune-Albright syndrome results from somatic mutations of the GNAS gene (G-protein a-subunit) especially mutations in Gsa (stimulatory G protein) (Dumitrescu and Collins 2008).…”
Section: Acquired Hyperpigmentation Disordersmentioning
confidence: 99%
“…POEMS syndrome ( polyneuropathy, organomegaly, endocrinopathy, M-protein, and skin changes) is a multisystem disorder associated with plasma cell dyscrasia, and patients with POEMS syndrome show up-regulated serum levels of angiogenetic factors including VEGF (vascular endothelial growth factor) and HGF (hepatocyte growth factor) (Yamada et al 2013). Cantu syndrome, characterized by hypertrichosis, macrosomia, osteochondrodysplasia, and cardiomegaly, is reported to be caused by mutations in ABCC9 (ATP-binding cassette, subfamily C, member 9) (van Bon et al 2012). McCune-Albright syndrome results from somatic mutations of the GNAS gene (G-protein a-subunit) especially mutations in Gsa (stimulatory G protein) (Dumitrescu and Collins 2008).…”
Section: Acquired Hyperpigmentation Disordersmentioning
confidence: 99%
“…Individuals affected by Cantú syndrome also tend to exhibit coarse facies, similar to acromegaly in appearance. The genetic basis of Cantú syndrome was elucidated by Van bon et al and Harkalova et al in 2012, who demonstrated that mutations in the ABCC9 gene appear to be causative of Cantú syndrome [2,3]. The ABCC9 gene encodes the channel regulation protein SUR2, which acts as part of an adenosine triphosphate-sensitive potassium channel.…”
Section: Discussionmentioning
confidence: 99%
“…Cantú syndrome has been considered as a new member of potassium channelopathies [van Bon et al, 2012]. The syndrome has been attributed to mutated ABCC9 or KCNJ8 genes as the underlying causes.…”
Section: Discussionmentioning
confidence: 99%
“…The facial appearance resembles acromegaloid syndromes or storage disorders [Harakalova et al, 2012;van Bon et al, 2012]. To date, about 50 cases with Cantú syndrome have been reported, and heterozygous pathogenic variants in the ABCC9 or the KCNJ8 genes have been found in 80% of the cases [van Bon et al, 2012;Czeschik et al, 2013].…”
mentioning
confidence: 99%
See 1 more Smart Citation